ANALISIS PENGARUH BRAND AWARENESS TERHADAP MINAT BELANJA DI MIXUE DAERAH TABANAN - Putra, I Putu Dharmawan Suryagita Susila; Mardika, Agus Putra; Dewi, Ida Ayu Indra Kencana (Universitas Tabanan, 2023)
Mixue is aggressively expanding its business with ice cream and tea in various countries, including Indonesia. Mixue in Indonesia is growing rapidly, seen from the increasing number of outlets in Indonesia, as well as in Tabanan district - Bali. In Tabanan there are already three mixue outlets. Tabanan community has a high interest in shopping for mixue products, the high interest in shopping is thought to be because the community already knows and recognizes the existence of the mixue brand before mixue was built in Tabanan. In this phenomenon, it is suspected that brand awareness has a significant influence on purchase intention, because of this the researcher examined how brand awareness affects purchase intention in the mixue Tabanan. In this study uses data collection techniques on various literatures, as well as various reports related to research variables, this study uses data collected by observation techniques in the form of direct observation at mixue outlets in the Tabanan, and interviews conducted by interviewing 5 people from generation Y and Generation Z in Tabanan. This study obtained results, namely the first brand identity affects shopping interest. Second, social media and word of mouth affect brand awareness, and third, brand awareness affects purchase intention.